Snapshot of Phylogenetic Groups, Virulence, and Resistance Markers in Escherichia coli Uropathogenic Strains Isolated from Outpatients with Urinary Tract Infections in Bucharest, Romania. (20th May 2019) - Cristea, Violeta Corina; Gheorghe, Irina; Czobor Barbu, Ilda; Popa, Laura Ioana; Ispas, Bogdan; Grigore, Georgiana Alexandra; Bucatariu, Irina; Popa, Gabriela Loredana; Angelescu, Maria-Cristina; Velican, Alexandra; Marutescu, Luminita; Popa, Marcela; et al.
Abstract : Background . Urinary tract infections (UTIs) caused by Uropathogenic Escherichia coli (UPEC) are among the most common infections worldwide, including Romania. To the best of our knowledge, this is the first study performed on a significant number of community-acquired (CA) UPEC strains isolated from Romanian outpatients, aiming to evaluate and establish potential correlations among the phylogenetic groups (PG), resistance profiles, and the virulence factors (VF) genes of the CA-UPEC isolates. Materials/Methods . The present study was performed on a total of 787 UPEC nonrepetitive isolates consecutively isolated during one month from outpatients with CA-UTIs, visiting one of the biggest laboratories in Bucharest, Romania, receiving patients from all over the country. The strains identification was performed by MALDI TOF and the susceptibility patterns were tested using Microscan according to CLSI guidelines. PCR assays were performed to detect the presence of different VFs ( fimH gene encoding for type 1 fimbriae, afaBC for A fimbriae, sfaDE for S fimbriae, KpsMTII for capsule, hlyA for haemolysin A, hlyD for haemolysin D, and cnf-1 for tumor necrosis factor), the phylogenetic groups (PG) A, B1, B2, and D, and the extended spectrum beta-lactamases (ESBLs) genes. Results . The 787 CA-UPEC strains were isolated predominantly from female patients (90.95%) of >30 years (~74%). The resistance rates were 47.52% for ampicillin, 41.16% for tetracycline, 24.39% for cotrimoxazole, 19.18% for amoxicillin-clavulanic acid, 15.50% for cefazolin, 14.99% for ciprofloxacin, and 14.86% for levofloxacin; 35.19% of the investigated strains were MDR and 9.03% ESBL producers (from which 42.25% were positive for bla CTX-M, 38.02% for bla TEM, and 19.71% for bla SHV). FimH was the most frequent virulence gene (93.90%) followed by hlyD (44.34%); afaBC (38.24%); KpsMTII (32.65%); sfaDE (23.88%); hlyA (12.45%); and cnf-1 (7.75%). The distribution of the analyzed UPEC strains in phylogenetic groups was different for non-MDR and MDR strains. Overall, 35% of the strains belonged to the phylogenetic group B2 (harboring the yjaA gene); 27% to group B1 (confirmed by the presence of the TspE4C2 fragment); 16% to group D; and 22% to group A. The CA-UPEC strains included in PG B1 and PG B2 proved to be the most virulent ones, the number of strains carrying multiple VFs (>3) being significantly larger as compared to strains belonging to PG A and PG D) (p<0, 0001). The presence of one or two ESBL genes was significantly associated (p =0.0024) with PGs A and D. Conclusions . Our findings showed that the community UPEC strains circulating in Bucharest, Romania, belong predominantly to group B2 and >90% harbored the fimH gene. High MDR resistance rates were observed, as well as extended VF profiles, highlighting the importance of this type of studies for improving the epidemiological surveillance and the therapeutic or prophylactic management of the respective infections, in the context of antibiotic resistance emergence.